A systematic review on the factors influencing adoption and consumption of orange-fleshed sweetpotato in sub-Saharan Africa - Idrissou Ahoudou; Dêêdi E. O. Sogbohossou; Dêêdi E. O. Sogbohossou; Vodjo Nicodème Fassinou Hotegni; Nadia Fanou-Fogny; Ismail Moumouni-Moussa; Enoch G. Achigan-Dako (Frontiers in Sustainable Food Systems)
Orange-fleshed sweet potato (OFSP) is a promising crop in combating vitamin A deficiencies (VAD) in sub-Saharan Africa (SSA)‘s vulnerable populations and its adoption directly impacts potential benefits across the value chains. This review assessed OFSP adoption factors and advances in research for OFSP increased production across SSA countries. Scopus, Research for Life, and Google Scholars were searched to identify peer-reviewed studies published between 2000 and 2023 on the different objectives. The systematic search resulted in 22 and 53 studies, respectively, for the first and second objective that met inclusion criteria. Data extracted include author and year, study location, study population, methodology, results, and conclusion. Our study indicates that the adoption of OFSP in SSA is influenced by six primary factors: “Knowledge and awareness,” “social factors and networks,” “agronomic traits,” “taste and sensory attributes,” “health and nutrition,” “market and economics.” Furthermore, the review identified various studies highlighting the need to align breeding objectives with factors influencing OFSP adoption, implement optimal agronomic practices tailored to local contexts, and develop efficient value chains and targeted marketing strategies to increase OFSP production and commercialization across sub-Saharan African countries. This review underscores the importance of formulating breeding objectives, production techniques, and commercialization strategies in line with stakeholder needs and adoption factors to ensure successful OFSP integration for combating VAD in SSA. With these insights into factors affecting adoption and consumption of biofortified crops, new research and development roadmap is required to address evolving challenges influencing widespread OFSP adoption.